Hegemoni Balian Desa dalam Aktivitas Ritual Hindu di Desa Pedawa - Mardika, I Putu; Pramiswara, I Gusti Agung Ngurah Agung Yudha; Kantina, Komang Agus Darmayoga (Jayapangus Press, 2025)
Balian Desa, a religious ritual leader who is trusted by the Bali Aga community, especially Pedawa Village. The Balian Desa position has vital duties and responsibilities in leading the procession of religious rituals of the Bali Aga community. In the perspective of Sociology, the position of the Balian Desa has the highest authority in terms of religious rituals carried out in Pedawa Village, the Balian Desa has enormous hegemonic power and has a strong influence on the continuity of community life in terms of religious ritual activities. This study aims to examine the hegemonic power possessed by a Balian Desa in the implementation of religious rituals that affect the community, especially in Pedawa Village. This research uses a qualitative approach with data collection methods in the form of observation, interviews, literature studies, and documentation. The results of this study show that a person who occupies a position as a Balian Desa has a great influence in the form of hegemony on religious ritual activities in Pedawa Village. This can be seen because the Balian Desa is chosen abstractly and through a sacred procession, and can legitimize every religious ritual. In addition, the hegemony of the village balian that influences the community is very strong through ideology, language, and folklore that strengthens people's trust in the Balian Desa figure, which has an impact on the socio-religious implications of the life of the Pedawa Village community. The conclusion of this research is that the Balian Desa has a strong position because it is chosen abstractly in the ritual aspect, in terms of hegemony, the village balian influences the ideology of the community through the form of language, sacred symbols, and beliefs (folklore) which make his position very strong, and this hegemony will have an impact on the socio-religious life of the Pedawa Village community.